The Relationship Between Time Management Skills and Academic Achievements of Nursing Students During the COVID-19 Pandemic - Sekizler, Emine Temizkan; Yildiz, Kerem; Gok, Nur Demet; Kahraman, Incihan; Orskiran, Bahar Ak; Kaya, Ufuk (Galenos Publ House, 2022)
Objective: This study aims to determine the relationship between the time management skills of nursing students and their academic achievements during the COVID-19 pandemic. Method:The The population of this descriptive study consisted of private University Health Sciences Faculty Nursing Department 2021-2022 Academic Year Fall Semester second year (n = 106), third year (n = 72), and fourth year (n = 88) students (n = 266). No sample selection was made in the study and the data were obtained from 182 students. The data of the study were collected online using the Participant Introduction Form and Time Management Questionnaire. Data analysis was performed using Statistical Package for Social Sciences 18.0 package software. Results: The mean score of the students on the time management inventory was found to be 90.93 +/- 11.67. A statistically significant difference was found between the overall Time Management Questionnaire mean score and the variables of presence of time-wasting factor during the distance education period (p = . 16) and duration of social media use (p = . 13, p < . 05). A statistical significance was found between the mean scores of the time attitudes sub- dimension and presence of time-wasting factor during the distance education period (p = . 001) and the duration of social media use (p = . 010, p < . 05). Conclusion: The students' time management skills were determined to be at a high level, the factors that caused time loss during the distance education period and the duration of social media use affected the time management skills, and the time management skills did not affect academic success.
International Scientific Research Congress -- APR 27-28, 2022 -- Baku, AZERBAIJAN
Keywords: Academic achievement; COVID-19 pandemic; nursing students; time management